2012
DOI: 10.1111/j.1467-8543.2012.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Labour Adjustment Implications of Service Offshoring: Evidence from Canada

Abstract: About one‐fifth of Canadian employees are in jobs that are vulnerable to service offshoring. Despite this figure, both theory and our empirical evidence (based on a variety of methodologies and datasets) suggest that the offshoring of business services is not likely to lead to large adverse employment effects. We also conclude that existing active labour market adjustment policies (e.g. increased labour market information, job search, mobility and training) developed for other adjustment pressures such as tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Within the ICT sector, offshoring affects certain areas very negatively. This confirms previous results regarding the effects of vertical disintegration on ERs, and that high-skilled undertaking more standardized jobs are vulnerable to offshoring (Bo¨ckerman and Maliranta, 2013;Doellgast and Greer, 2007;Gomez et al, 2013;Hummels et al, 2014;Norlander et al 2015). However, also within medico, where new jobs are created abroad, does managements' use of new pools of skilled workers abroad result in pressure on the bargaining position of the high skilled in the home company.…”
Section: Cross Sector Comparison and Conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…Within the ICT sector, offshoring affects certain areas very negatively. This confirms previous results regarding the effects of vertical disintegration on ERs, and that high-skilled undertaking more standardized jobs are vulnerable to offshoring (Bo¨ckerman and Maliranta, 2013;Doellgast and Greer, 2007;Gomez et al, 2013;Hummels et al, 2014;Norlander et al 2015). However, also within medico, where new jobs are created abroad, does managements' use of new pools of skilled workers abroad result in pressure on the bargaining position of the high skilled in the home company.…”
Section: Cross Sector Comparison and Conclusionsupporting
confidence: 92%
“…During the 1990s offshoring gained momentum in services. Research initially indicated that service offshoring produced only small negative effects on total employment, and apparently favoured highly skilled employees (Crinó, 2009; Gomez et al., 2013). However, studies have found evidence that offshoring impacts on the wages of individual highly skilled employees, but that the effect is conditional on the type of skill, with mainly highly skilled employees performing routine tasks suffering wage losses from offshoring (Gomez et al., 2013; Hummels et al., 2014).…”
Section: International Company Restructuring and Ers: A Conceptual Frmentioning
confidence: 99%
“…() claim that managers opposed unions not only to increase their own flexibility and the productivity of their workers, but also to reduce pay and benefits, either in absolute terms or relative to their previous growth rates. Some recent research has found that an increased reliance on offshore production has reduced wages for workers in similar industries (Autor et al ., and Ebenstein et al ., ), a finding supported in this paper, although other research (such as Gomez et al ., ) finds less of an effect, at least for service sector employees.…”
Section: Introductionmentioning
confidence: 92%
“…In industrial relations there have been various sector‐specific studies on the effects on wages, employment (Gomez et al . on Canadian business services) and worker morale (e.g. McCann on UK banking and insurance), but there is little research on the overall distribution of income in the economy.…”
Section: Comments On the Literaturementioning
confidence: 99%